2012
DOI: 10.1164/rccm.201202-0200oc
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Positive Airway Pressure Treatment of Sleepy Patients with Milder Obstructive Sleep Apnea

Abstract: Rationale: Twenty-eight percent of people with mild to moderate obstructive sleep apnea experience daytime sleepiness, which interferes with daily functioning. It remains unclear whether treatment with continuous positive airway pressure improves daytime function in these patients. Objectives: To evaluate the efficacy of continuous positive airway pressure treatment to improve functional status in sleepy patients with mild and moderate obstructive sleep apnea. Methods: Patients with self-reported daytime sleep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(78 citation statements)
references
References 27 publications
2
75
0
1
Order By: Relevance
“…The domain which was most notably affected was general productivity, which includes concentration, completing daily tasks and chores, remembering, working on hobbies, completing financial affairs and paperwork, employment tasks, and maintaining telephone conversations. Contextually, these scores were similar to those in individuals with mild sleep apnea [21] and worse than in patients suffering excessive daytime sleepiness due to congestive heart failure [23], chronic obstructive pulmonary disease with nocturnal hypoxemia [24], traumatic brain injury [22], and geriatric patients with self-reported sleepiness [25]. Additionally, the low FOSQ-10 scores may reflect the impact of sleepiness on daytime activities, including interactions with the ICU medical team, which is further evidenced by the association we found between perceived poor physician communication and cognitive blunting.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The domain which was most notably affected was general productivity, which includes concentration, completing daily tasks and chores, remembering, working on hobbies, completing financial affairs and paperwork, employment tasks, and maintaining telephone conversations. Contextually, these scores were similar to those in individuals with mild sleep apnea [21] and worse than in patients suffering excessive daytime sleepiness due to congestive heart failure [23], chronic obstructive pulmonary disease with nocturnal hypoxemia [24], traumatic brain injury [22], and geriatric patients with self-reported sleepiness [25]. Additionally, the low FOSQ-10 scores may reflect the impact of sleepiness on daytime activities, including interactions with the ICU medical team, which is further evidenced by the association we found between perceived poor physician communication and cognitive blunting.…”
Section: Discussionmentioning
confidence: 58%
“…We found that excessive daytime sleepiness is common among family members of the critically ill. Over half of our subjects reported significant daytime sleepiness [9], demonstrating sleepiness similar to patients with obstructive sleep apnea [11, 21]. Thus, the proportion of significant daytime sleepiness (50.2 %) in these subjects is striking and considerably greater than in the general population (10–20 %) [8].…”
Section: Discussionmentioning
confidence: 93%
“…This provided a ready target for treatment with CPAP and mandibular advancement devices which improve EDS [35]. Compared to those without sleepiness, treatment of patients with EDS has also been shown to reduce blood pressure, vascular risk [5, 10, 11], and improve quality of life [36]. Thus it has been proposed that OSA with EDS is a unique phenotype [37].…”
Section: Potential Clinically Relevant Osa Phenotypesmentioning
confidence: 99%
“…Among patients who tolerate PAP, results are excellent; however, effectiveness is limited by variable adherence. 34 Improvements in our understanding of OSA pathogenesis have led to a concept that the mechanism (endotype) underlying OSA is highly variable across individuals such that some patients have primarily an upper airway anatomical problem, whereas others have dysfunction in upper airway dilator muscles, some have unstable control of breathing and some may have combinations of abnormalities. 1 This realisation has led to the concept of personalised medicine in OSA such that therapies could theoretically be targeted to the mechanism underlying apnoea rather than using a ‘one-size-fits-all’ approach.…”
mentioning
confidence: 99%